Народництво і модернізм в інтерпретації літературних критиків журналу «Украинская жизнь» (1912-1917) - Полумисна, О.О. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2007)
Изучены тенденции в освещении народнической и модернистской литературы в критике журнала «Украинская жизнь»(1912-1917). The attempt to investigate the tendencies that were the main at the pages of Ukrainian-Russian journal „Ukrajinskaja ghysn" (1912-1917) was made at the field of narodnik and modernist literature.
Keywords: журнал "Украинская жизнь"; народництво; модернізм; література «для хатнього вжитку»